The Effect of Digital Literacy on Learning Quality and Instructional Innovation: A Structural Equation Modeling Approach in Secondary Education - Wulida Emeris; Dimas Nugraha; Dimas Febrian; Aslamiah Siregar (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to examine the effect of digital literacy on learning quality and instructional innovation using a Structural Equation Modeling (SEM) approach in secondary education. Digital literacy is positioned as an exogenous variable, while learning quality and instructional innovation function as endogenous variables. The research employs a quantitative design with a survey method involving secondary school students. Data were collected through a structured questionnaire and analyzed using SEM to identify the relationships among variables. The findings indicate that digital literacy has a significant positive effect on learning quality and instructional innovation. Students with higher levels of digital literacy tend to demonstrate better engagement, deeper understanding of learning materials, and greater participation in innovative learning activities. Furthermore, digital literacy also indirectly contributes to enhancing instructional innovation through improved learning quality. These results highlight the importance of integrating digital literacy into educational practices to support effective and innovative learning in the era of educational transformation.